Analisis Faktor-Faktor yang Mempengaruhi Keputusan Go-Around oleh Siswa Penerbang dalam Kondisi Gusty Wind di Runway Bandar Udara Banyuwangi - Sitompul, Binsar Parulian; Hari Kurniawanto; Budi Hartono; Rifki Arif; Eva Magdelana BR. Simamora (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study originates from the difficulties student pilots encounter when deciding to perform a go-around during unstable strong wind (gusty wind) conditions, especially on the runway at Banyuwangi Airport. The go-around procedure is a vital element in maintaining flight safety, but for inexperienced students, the decision is often challenging and influenced by multiple factors. The purpose of this research is to explore and analyze the aspects that affect student pilots’ considerations when faced with gusty wind situations. Using a descriptive qualitative method, data were gathered through semi-structured interviews with both student pilots and flight instructors. The findings reveal that several elements play key roles in shaping decision-making, including the level of flight experience, the application of aeronautical decision-making (ADM) principles, situational awareness in rapidly changing conditions, and the psychological pressures experienced during critical phases of flight. These insights emphasize the importance of strengthening pilot training programs, particularly in weather-related decision-making scenarios. By integrating structured ADM training and enhancing awareness of environmental factors, student pilots can be better prepared to respond to challenging conditions. The outcomes of this research are expected to support improvements in aviation education, reduce potential risks, and foster a stronger safety culture among future pilots.